Portrait of Richard Scott Perkin (1906-1969) - Perkin-Elmer Corporation (1960)
Portrait of American entrepreneur Richard Scott Perkin (1906-1969). In 1937, Richard Perkin and Charles Elmer (1872-1954) founded the Perkin-Elmer Corporation, an optical design and consulting company that later expanded into the manufacture of analytical and astronomical instruments.
Keywords: Portrait photography; Perkin, Richard Scott, 1906-1969; Perkin-Elmer Corporation; Portraits; Corporations